2013
DOI: 10.3386/w18818
|View full text |Cite
|
Sign up to set email alerts
|

Home Computers and Child Outcomes: Short-Term Impacts from a Randomized Experiment in Peru

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Reading should improve children's reading recognition skills. Computer use may have positive affect both types of cognitive skills and television may improve reading skills (Fiorini 2010; Malamud and Pop-Eleches, 2011; Beuermann et al, 2013; Gentzkow and Shapiro, 2008; Huang and Lee, 2010). Some active leisure activities, for example, team sports and educational games, may also positively affect cognitive skills.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Reading should improve children's reading recognition skills. Computer use may have positive affect both types of cognitive skills and television may improve reading skills (Fiorini 2010; Malamud and Pop-Eleches, 2011; Beuermann et al, 2013; Gentzkow and Shapiro, 2008; Huang and Lee, 2010). Some active leisure activities, for example, team sports and educational games, may also positively affect cognitive skills.…”
Section: Datamentioning
confidence: 99%
“…Fiorini and Keane (2014) find that time spent on media is as important input in cognitive skill production as after-school care. According to the findings of Fiorini (2010), Malamud and Pop-Eleches (2011), and Beuermann et al (2013), computer use fosters verbal and nonverbal intelligence. Gentzkow and Shapiro (2008) and Huang and Lee (2010) conclude that moderate television watching improves children's reading ability.…”
Section: Introductionmentioning
confidence: 99%
“…Fairlie and Robinson (2013) report the results of a randomized trial involving younger students in Grades 6-10. There have also been two studies of the rollout of the One Laptop Per Child (OLPC) initiative in rural Peru (Beuermann et al 2013;Cristia et al 2012). While these studies often report positive outcomes of computer access on some outcomes, they typically report no or modest impacts on basic academic indicators.…”
Section: Cps: Current Population Survey Dsl: Digital Subscriber Line mentioning
confidence: 99%
“…Another identified that the use of the Internet at home for learning and communication, not playing and browsing, were associated with higher cognitive scores (Johnson, 2009). However, not all research articles identified a positive effect on cognitive development, a study that explored one laptop per child scheme in Peru found no significant increase in cognitive development for participants (Beuermann et al, 2013). Like academic achievement, how the Internet is used appears to influence its value with regards to cognitive development.…”
Section: Subjectification: Strengthening Individualitymentioning
confidence: 98%